The Influence of Employee Competency, Work Environment, and Work Discipline on Employee Perfomance - Rahmawati, Heni; Mardiana, Tri (Universitas Mercu Buana, 2024)
This study aims to determine the effect of Employee Competency, Work Environment, Work Discipline on Employee Perfomance PT Bima Multifinance Yogyakarta. The data collection technique used is the census technique or saturated sampling using a questionnaire. The Data analysis techniques through classical assumption tests and multiple linear regression analysis using SPSS 25. This research is a casual associative research using a quantitative approach. The population in this study were all employees at the PT Bima Multifinance Yogyakarta. The number of samples used in this study were 62 respondents. The results of this study reveal that employee competency, work environment, and work discipline have a joint effect on employee performance at the PT Bima Multifinance Yogyakarta, and Work discipline the most dominant influence on employee performance.